IVF outcomes of embryos with abnormal PGT-A biopsy previously refused transfer: a prospective cohort study - Barad, D H; Albertini, D F; Molinari, E; Gleicher, N (Human reproduction (Oxford), 2022)
What are the outcomes for patients who choose to move embryos diagnosed as abnormal by preimplantation genetic testing for aneuploidy (PGT-A) to a new institution for transfer after the diagnosing institution refused to transfer them? Many patients seek to have selected embryos with PGT-A abnormal trophectoderm biopsies transferred recognizing that these embryos can still offer a chance of pregnancy and live birth. : PGT-A is a widely practiced method of selecting embryos for transfer based on biopsy of a few cells. Many clinical practices refuse to transfer PGT-A abnormal embryos even when there are no other 'normal' embryos available. This is a prospective cohort of 69 couples who, since 2014, moved a total of 444 PGT-A abnormal embryos previously refused transfer at their parent institutions to our practice. Among these, 50 patients have, thus far, undergone 57 transfer cycles of 141 embryos. Embryos diagnosed at other institutions by PGT-A as abnormal (mostly using next generation sequencing) were moved to our academically affiliated private fertility and research center in New York City. Female age at retrieval was 41.35 ± 3.98 years, 74% were Caucasian, 12% Asian and 10% were of African descent. All embryos identified as PGT-A abnormal among prospectively identified couples were recorded in our center's registry. Among the 144 embryos transferred 102 (72.3%) had only 1 or 2 chromosomal abnormalities, 30 (21.3%) had 3 or more and 9 (6.4%) were 'undiagnosed' because of degraded DNA, yet still had been refused transfer. Transfer of PGT-A abnormal embryos resulted in 8 live births, 11 miscarriages and no voluntary terminations. One child was born with a segmental duplication and required repair of coarctation of the aorta as a newborn. Many couples with only PGT-A abnormal embryos are willing to have their PGT-A abnormal embryos transferred and such transfers can result in the establishment of ongoing euploid pregnancies and live births. Findings in this case series represent couples who chose to have their embryos transferred after having been refused transfer elsewhere and may not be representative of the wider population of couples undergoing IVF with PGT-A in general. Not all abnormal phenotypes present in the immediate postnatal period so it will be important to continue to follow the development of these children. PGT-A can result in a clinics refusal to transfer embryos with abnormal PGT-A biopsies, even those with mosaic findings, consequently large numbers of infertile women are prematurely advised that their only chance of motherhood is through third-party egg-donation. This work was supported by intramural funds from the Center for Human Reproduction and the not-for-profit research Foundation for Reproductive Medicine, both in New York, NY, USA. N.G. and D.H.B. are listed as co-inventors on several U.S. patents. One of these patents (US Patent# 7,615,544) relates to pre-supplementation of hypo-androgenic infertile women with androgens, such as DHEA and testosterone and, therefore, at least peripherally related to the subject of this manuscript. N.G. and D.F.A. also received travel funds and speaker honoraria from several pharmaceutical and medical device companies, though none related to the here presented subject and manuscript. N.G. is a shareholder in Fertility Nutraceuticals and he and D.H.B. receive royalty payments from Fertility Nutraceuticals LLC. N/A.